ANALYSIS OF A COMBINED BRAYTON/RANKINE CYCLE WITH TWO REGENERATORS IN PARALLEL - Santos, J. T. dos; Fagundes, T. M.; Santos, E. D. dos; Isoldi, L. A.; Rocha, L. A. O. (Revista de Engenharia Térmica, 2017)
This work presents a configuration of two regenerators in parallel for a power generation Brayton/Rankine cycle where the output power is 10 MW. The working fluids considered for the Brayton and Rankine cycles are air and water, respectively. The addition of a regenerator with the previous existing cycle of this kind resulted in the addition of a second-stage turbine in the Rankine cycle of reheat. The objective of this modification is to increase the thermal efficiency of the combined cycle. In order to examine the efficiency of the new configuration, it is performed a thermodynamic modelling and numerical simulations for both cases: a regular Brayton/Rankine cycle and the one with the proposed changes. At the end of the simulations, the two cycles are compared, and it is seen that the new configuration reaches a 0.9% higher efficiency. In addition, the vapor quality at the exit of the higher turbine is higher, reducing the required mass flow rate in 14%.